(untitled) (Bangladesh Journal of Zoology, 2022)
This study was conducted to investigate the fish diversity and livelihood condition of fishermen community at Dangapara village of Halti beel, Singra, Natore. The socio-economic data were collected from 50 randomly selected fishermen using questionnaire survey between July and October 2019. In this study, a total of 43 fish species were recorded under seven orders, 20 families and 32 genera. Majority of fishermen were illiterate (44%), about 28% fishermen could sign only, 24% and 4% fishermen were completed primary and secondary education, respectively. Among them 79% were Muslims and 21% were Hindus. The majority of fishermen had mud house with straw and tin roof while 56% household used tin roof, 34% household used tin shed with tin roof, only 10% household used straw. Fishermen annual income was between 30001 to 40000 BDT. About 66% household had kacha toilets, 30% household had semi paka toilets, only 4% household had no sanitary facilities. The most of the households (78%) were used electricity as their energy source. The majority of fishermen (64%) were received health service from village doctors. About 44% fishermen was directly engaged in fishing as their main occupation while 26% and 24% fishermen were engaged in labor and agriculture activities, only 8% fishermen was engaged in other professions. Bangladesh J. Zool. 50 (1): 37-49, 2022